Fabrication of Pr-PVP-Co-Doped NanoTiO2 Film on Titanium Matrix with Outstanding Electrocatalytic Reduction Activity for Oxalic Acid. Issue 9 (14th July 2017) - Song, Wenliang; Zhang, Yu; Jin, Hua; Kim, Mi-Ra; Kim, Seok; Kim, Il
Abstract : A highly active and stable praseodymium-polyvinylpyrrolidone (Pr-PVP)-co-doped nanoTiO2 film/titanium matrix was successfully fabricated for the electrocatalytic reduction of oxalic acid. The structure, morphology, and electro catalytic activity of the as-synthesized Pr-PVP-doped nanoTiO2 film on a titanium matrix surface was studied with X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy, cyclic voltammetry, and electrochemical impedance spectroscopy. The electro catalytic properties were assessed by studying the electro reduction of oxalic acid on Pr-PVP-co-doped nanoTiO2 film electrodes. The results showed a high yield of glyoxylic acid (82.6%) and a high current efficiency (81%) with galvanostatic preparative reduction. Based on the results, Pr-PVP-modified nanoTiO2 film has a large electrochemical active surface area and small charge transfer resistance. The good electro catalytic performance of Ti/Pr-PVP-nano TiO2 makes it promising for use as an electrode in the electro catalytic reduction of oxalic acid.